Composting as a sustainable option for managing biomass of aquatic weed Pistia: A biological hazard to aquatic system. (10th March 2018) - Gusain, Rita; Pandey, Bhawna; Suthar, Surindra
Abstract: The composting is one of the effective tools to convert organic solid wastes into an added-value product for the agronomic application. In this study, the aquatic weed Pistia sp. (water lettuce) biomass was co-composted with cow dung in 1:1 and 3:1 ratio and changes in physicochemical properties were measured during the process. One setup with 100% plant biomass was also kept to see scaling impact of cow dung on composting process. The composting was performed in rectangular plastic crates of 50 kg capacity under ambient conditions. A decrease in pH (0.21–4.57%), total organic carbon (2.42–22.5%) and, carbon to nitrogen ratio (15.59–41.13%) ratio and increase in total N (15.61–22.14%), total P (29.75–50.67%), total K (30.3–81.59%), total calcium (15.17–26.07%), zinc (26.07–42.72%), iron (16.39–24.26%) and, copper (29.18–34.18%) were recorded during the composting process. The results of the microbial enzyme (dehydrogenases, protease and phosphate) suggested the high rate of microbial activities and organic matter mineralisation during the composting process. The seed germination index and soil respiration rate suggested the non-phytotoxic and microbially stable properties of composted waste mixtures. The maximum waste mineralisation was in compost setup with 50% proportion of plant biomass. Results suggest that composting can be a cleaner option to convert aquatic weed biomass into added-value materials for sustainable agriculture programs. Graphical abstract: Highlights: Aquatic weed Pistia biomass was composted after mixing in cow dung (CD). Analyzed variables indicates the quality of compost for agronomic applications. Pistia with CD in ratio, 1:1 showed the best results of chemical quality. Germination index and soil respiration indicates stability and non-phytoxic properties of final material.